Do natural disasters accelerate sustainability transitions? Insights from the Central Italy earthquake. Issue 11 (2nd November 2022) - Rizzo, Annalisa; Cappellano, Francesco; Pierantoni, Ilenia; Sargolini, Massimo
ABSTRACT: This paper examines whether natural disasters open a policy window of opportunity for sustainable transition in lagging regions. Bridging disaster studies and the transition management approach, the authors define the Post-Disaster Policy Window of Opportunity (PPWO) concept, as a heuristic tool to assess the acceleration of a sustainable transition generated by a shock. The paper applies PPWO to the case study of the Central Italy earthquake (2016) deploying both primary and secondary data concerning public policies designed to pursue societal challenges at regional levels. The authors examine (i) the governance scheme, (ii) the objectives, and (iii) the policy implementation strategy of the transition as agreed in a pre-disaster phase, and whether they changed during the disaster and in its aftermath. The findings highlight natural disasters per se cannot prompt a radical change to territorial development patterns in lagging regions. However, disasters' potential to spur sustainable transitiońs acceleration can be enabled through a place-based approach with a coherent vertical and horizontal policy coordination.